The Concept of Cooperative Dynamics in Simulations of Soft Matter - Polanowski, Piotr; Sikorski, Andrzej (Frontiers in Physics, 2020)
In this review we compiled recent theoretical advances concerning the diffusive motion in crowded soft matter systems. We tried to answer a question how to effectively perform dynamic Monte Carlo simulations of dense macromolecular systems. This problem is not simple due to the fact that the movement in such systems is strictly correlated which leads to cooperative phenomena. The influence of crowding was found especially interesting in two-dimensional cases, e.g. in membranes where the presence of macromolecules, proteins and cytoskeleton often changed the mean-square displacement as a function of the lag time and anomalous diffusion appeared. Simple models are frequently used to shed a light on transport in biological systems. The emphasis was given to the Dynamic Lattice Liquid (DLL) model. The latter model became a basis for a parallel algorithm which takes into account coincidences of elementary molecular motion attempts resulting in local cooperative structural transformations. The emphasis is put on influence of the model of molecular transport on the diffusion and the dynamic scaling behavior. A comparison to alternative approaches like single agent model was carried out.